Hazardous contaminants in plastics contained in compost and agricultural soil. (April 2022) - Scopetani, Costanza; Chelazzi, David; Cincinelli, Alessandra; Martellini, Tania; Leiniö, Ville; Pellinen, Jukka
Abstract: Macro-, meso- and microplastic (MAP, MEP, MP) occurrence in compost is an environmental issue whose extent and effects are not yet understood. Here, we studied the occurrence of MAPs, MEPs and MPs in compost samples, and the transfer of hazardous contaminants from plastics to compost and soil. MAPs/MEPs and MPs concentrations in compost were 6.5 g/kg and 6.6 ± 1.5 pieces/kg; from common recommendations for compost application, we estimated ∼4–23 × 10 7 pieces MPs and 4–29 × 10 4 g MAPs/MEPs ha −1 per year ending into agricultural soils fertilized with such compost. Regarding contaminants, bis(ethylhexyl) phthalate, acetyl tributyl citrate, dodecane and nonanal were extracted in higher concentrations from plastics and plastic-contaminated compost than from compost where MAPs/MEPs had been removed prior to extraction and analysis. However, some contaminants were present even after MAPs/MEPs removal, ascribable to short- and long-term release by MAPs/MEPs, and to the presence of MPs. DEHP concentration was higher in soils where compost was applied than in fields where it was not used. These results, along with estimations of plastic load to soil from the use of compost, show that compost application is a source of plastic pollution into agricultural fields, and that plastic might transfer hazardous contaminants to soil. Graphical abstract: Image 1 Highlights: MAPs/MEPs and MPs concentration in the compost: 6.5 g/kg dw and 6.6 ± 1.5 items/g dw. MPs load estimation: 4, 6 × 10 7 to 2, 3 × 10 8 items ha −1 yr −1 into agricultural soils. MAPs/MEPs-containing compost had significantly higher concentration of DEHP. Compost can represent a source of plastic contamination to the agricultural fields.